Does Investment Diversification Enhance Profitability? Evidence from Nepal’s Non-life Insurance Sector - Upadhyaya, Yadav Mani; Kharel, Khom Raj (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study aims to analyze the effect of investment diversification on the profitability of non-life insurance firms in Nepal, considering recent structural reforms and mergers. Design/methodology/approach: This study employs a quantitative, explanatory research design using panel data from 14 non-life insurance companies in Nepal over five fiscal years (2019/20–2023/24), with secondary data sourced from yearly reports of non-life insurance companies in Nepal. Regression methods using panel data have been used to study how investment affects profitability, taking into account past financial data and changes over time for each company. Findings: The results indicate that both investment (current and lagged) and total premium have a statistically significant and positive impact on the net profit of non-life insurance companies in Nepal, while employment shows no significant effect. Conclusion: Boosting profitability in Nepal’s non-life insurance sector requires a strategic emphasis on investment efficiency and premium growth through innovation and market expansion. Prioritizing employee productivity over workforce expansion, coupled with data-driven decision-making, will enable insurers to achieve sustainable long-term profitability. Implications: Policies should promote efficiency and productivity in human resource management rather than incentivizing workforce expansion, aligning with the sector’s long-term profitability and sustainability goals. Originality/value: This study uniquely analyzes investment diversification’s profitability impact in Nepal’s post-merger non-life insurance sector, revealing lagged investment effects and premium growth as key drivers, with actionable insights for emerging markets. JEL Classification: C33, O16, G11, G22